Effects of Kiwifruit Rootstocks with Opposite Tolerance on Physiological Responses of Grafting Combinations under Waterlogging Stress - Danfeng Bai; Zhi Li; Shichao Gu; Qiaohong Li; Leiming Sun; Xiujuan Qi; Jinbao Fang; Yunpeng Zhong; Chungen Hu (Plants, 2022)
Kiwifruit is commonly sensitive to waterlogging stress, and grafting onto a waterlogging-tolerant rootstock is an efficient strategy for enhancing the waterlogging tolerance of kiwifruit plants. KR5 (Actinidia valvata) is more tolerant to waterlogging than ‘Hayward’ (A. deliciosa) and is a potential resistant rootstock for kiwifruit production. Here, we focused on evaluating the performance of the waterlogging-sensitive kiwifruit scion cultivar ‘Zhongmi 2′ when grafted onto KR5 (referred to as ZM2/KR5) and Hayward (referred to as ZM2/HWD) rootstocks, respectively, under waterlogging stress. The results showed ‘Zhongmi 2′ performed much better when grafted onto KR5 than when grafted onto ‘Hayward’, exhibiting higher photosynthetic efficiency and reduced reactive oxygen species (ROS) damage. Furthermore, the roots of ZM2/KR5 plants showed greater root activity and energy supply, lower ROS damage, and more stable osmotic adjustment ability than the roots of ZM2/HWD plants under waterlogging stress. In addition, we detected the expression of six key genes involved in the kiwifruit waterlogging response mechanism, and these genes were remarkably induced in the ZM2/KR5 roots but not in the ZM2/HWD roots under waterlogging stress. Moreover, principal component analysis (PCA) further demonstrated the differences in the physiological responses of the ZM2/KR5 and ZM2/HWD plants under waterlogging stress. These results demonstrated that the KR5 rootstock can improve the waterlogging tolerance of grafted kiwi plants by regulating physiological and biochemical metabolism and molecular responses.